2023
DOI: 10.3390/foods12030662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flaxseed Mucilage and Gum Arabic on Probiotic Survival and Quality of Kefir during Cold Storage

Abstract: This study aimed to assess the survival of probiotic cultures in kefir. Kefir is a fermented dairy product, and in this study we incorporated nutritionally rich flaxseed mucilage and gum arabic as a prebiotic, then monitored for improvement in the the viability of Lactobacillus acidophilus and Bifidobacterium lactis. In addition, some physicochemical variables of kefir were investigated. The addition of flaxseed mucilage and gum arabic significantly (p ˂ 0.05) increased the growth of both Lactobacillus acidoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several studies have confirmed the prebiotic function of FM complemented by the potential to change gut microbiota composition leading to positive health effects. For instance, Alhssan et al (2023) observed the improvement in the viability of Lactobacillus acidophilus and Bifidobacterium lactis in cold-stored kefir, suggesting FM's role as a prebiotic. Another study described an increased proportion of Akkermansia and Bifidobacterium within a high-fat diet supplemented by FM in mice.…”
Section: Beneficial Changes Of Gut Microbiota Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed the prebiotic function of FM complemented by the potential to change gut microbiota composition leading to positive health effects. For instance, Alhssan et al (2023) observed the improvement in the viability of Lactobacillus acidophilus and Bifidobacterium lactis in cold-stored kefir, suggesting FM's role as a prebiotic. Another study described an increased proportion of Akkermansia and Bifidobacterium within a high-fat diet supplemented by FM in mice.…”
Section: Beneficial Changes Of Gut Microbiota Compositionmentioning
confidence: 99%
“…For instance, Alhssan et al . (2023) observed the improvement in the viability of Lactobacillus acidophilus and Bifidobacterium lactis in cold‐stored kefir, suggesting FM's role as a prebiotic. Another study described an increased proportion of Akkermansia and Bifidobacterium within a high‐fat diet supplemented by FM in mice.…”
Section: Food and Nutritional Applicationsmentioning
confidence: 99%
“…In food packaging, mucilage's adhesive nature provides a basis for biodegradable adhesives and the production of edible food coatings and films. It has shown protection against the permeability of oxygen and moisture and also has favorable functional attributes such as tensile strength and durability (4, [10][11][12][13]. Its moisture-retention properties help prolong the freshness of perishable foods.…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of kefir samples with pure flaxseed mucilage significantly enhanced the viability of LAB at the end of the storage period [23]. The addition of flaxseed mucilage and gum arabic has been shown to increase the survival of probiotic cultures Lactobacillus acidophilus and Bifidobacterium lactis in kefir and change the physicochemical properties of the product, in particular, increasing its viscosity [25,26]. In general, adding seed gum, mucilage, powder, or guar to fermented dairy foods, particularly yogurt, significantly improves the structure and consistency (thickens, emulsifies, and forms a gel), increases the moisture-holding power, and reduces syneresis [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%